Conglutinin acts as an opsonin for influenza A viruses - Hartshorn, KL; Sastry, K; Brown, D; White, MR; Okarma, TB; Lee, YM; Tauber, AI (The Journal of immunology (1950), 1993)
Since the 1940's, non-Ig inhibitors of influenza A virus (IAV) hemagglutination activity and infectivity have been recognized in mammalian sera. Recently, the heat labile (beta) inhibitor of this type was identified by indirect methods as the lectin, conglutinin. In support of this hypothesis, we found that purified conglutinin strongly inhibited hemagglutination activity and infectivity of IAV. By using IAV strains with specific variations in glycosylation of the hemagglutinin molecule, we showed these effects to be mediated by binding of conglutinin to high mannose carbohydrate attachments on the viral hemagglutinin. Through the same mechanism conglutinin caused aggregation of IAV particles. Human neutrophils produce hydrogen peroxide upon exposure to IAV. Also, after a brief period of exposure to IAV, neutrophils exhibit depressed responsiveness (deactivation) upon exposure to other stimuli (e.g., chemotactic peptides). These phenomena may be related to the in vivo inflammatory response during IAV infection, and to the propensity of IAV-infected subjects to suffer bacterial superinfection. Pre-incubation of IAV with conglutinin markedly potentiated human neutrophil hydrogen peroxide production in response to the virus. This effect correlated with the ability of conglutinin to aggregate the virus. IAV treated with conglutinin also caused significantly less neutrophil deactivation than did the unopsonized virus. These enhancements of neutrophil respiratory burst responses by conglutinin were again mediated by binding of the lectin to viral carbohydrates. The mammalian C-type lectin family includes conglutinin, mannose-binding protein, and surfactant proteins A and D. These lectins may be important constituents of the initial host response to IAV, by inhibiting IAV infectivity directly, causing viral aggregation, and acting as opsonins to enhance phagocyte responses to the virus.